TINJAUAN YURIDIS SURAT PERINTAH PENGHENTIAN PENYIDIKAN BERUPA PENERBITAN KETERANGAN LUNAS BANK INDONESIA - Rachma Aulia Putri Yusuf Darmawan; Abdul Ficar Hadjar (Fakultas Hukum Universitas Trisakti, 2022)
In Law of the Republic of Indonesia No. 19 of 2019 concerning the Second Amendment to Provisions No. 30 of 2002 Concerning the Corruption Eradication Commission, Article 40 of Law No. 19 of 2019 regulates certainty regarding the KPK. The most recent KPK law gives the KPK permission to stop investigations, in contrast to earlier requirements. Definition of the issue: The KPK has the authority to issue an investigation termination (SP3) on cases of criminal acts of corruption in the form of Publication of a Certificate of Settlement (SKL) to the Bank Indonesia and Issuance of a Certificate of Payment (SKL) Against Bank Indonesia Liquidity Assistance Obligors (BLBI). in accordance with Law No. 19 of 2019 on the Corruption Eradication Commission of the Republic of Indonesia (KPK), Liquidity Assistance Obligor (BLBI). Legal-normative research methodology is employed. Qualitative data analysis methodologies. Concluding things using the deductive approach. Research findings, analysis, and conclusions In order to establish legal clarity and reduce abuse of power, it is important that the Corruption Eradication Commission be granted the authority to create an Investigation Termination Letter (SP3). Additionally, the approval of SP3 for the Corruption Eradication Commission appears to be ineffectual, particularly because it restricts and obstructs the space available for the Commission in the Corruption Eradication application.